2020
DOI: 10.1093/ofid/ofaa117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Risk Factors for Tunneled Hemodialysis Catheter-Related Bloodstream Infections

Abstract: Diabetes and left internal jugular vein insertion site were significantly associated with increased risk of a catheter-related bloodstream infection from a tunneled hemodialysis catheter. Ex-smoker status was significantly associated with reduced risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
2
12
3
3
Order By: Relevance
“…Gram positive organisms are responsible for most CRBSI episodes associated with TCCs (40–84% cases). 16 Our CRBSI microbiology results are consistent with the international literature since gram-positive organisms were the most prevalent isolates (60.4%) (Figure 4). However, Candidemia was found in a significant proportion of patients (26%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gram positive organisms are responsible for most CRBSI episodes associated with TCCs (40–84% cases). 16 Our CRBSI microbiology results are consistent with the international literature since gram-positive organisms were the most prevalent isolates (60.4%) (Figure 4). However, Candidemia was found in a significant proportion of patients (26%).…”
Section: Discussionsupporting
confidence: 90%
“…Recently Martin et al from Melbourne, Australia published their findings that presence of diabetes and left internal jugular vein insertion site were independent risk factors for CRBSI. 16 Seventeen percent of the TCCs in their study were associated with CRBSI leading to removal of catheter in 16% cases. Castro et all reported a higher infection rate associated with TCCs (29.6%), with the mean catheter duration of 333 days explaining the higher frequency of infection.…”
Section: Discussionmentioning
confidence: 92%
“…Variation in infection rate among different studies could be due to multiple causes, mainly because of differed health settings and patients' attitude. Previously conducted studies reported that risk of CRBSI was signi cantly higher among patients with catheter placement from left internal jugular vein, diabetes, increasing catheter duration [31,32]. However, in the current study no signi cant association of any factor was determined with CRI.…”
Section: Discussioncontrasting
confidence: 69%
“…While it has been lately reported by Quinn et al, in one Canadian study, that CRBSIs culminated into death of 2.3% of their cohort, 39 Farrington and Allon affirmed that only 1% of the recorded mortality between their catheter-reliant hemodialysis patients was ascribed to CRBSI. 37 Recently, a substantively higher mortality rate up to 5% was specified by Martin et al 40 In contrast, although 2.16% of our hemodialysis patients died during the 2 years-study period, mortality could not be allocated directly to CRBSI, denoting that the use of hemodialysis catheters was not a leading cause of death per se amongst our cohort.…”
Section: Discussionmentioning
confidence: 66%